A influência das relações academia-indústria no desenvolvimento tecnológico: um estudo das relações da Petrobras com instituições de ciência e tecnologia do Estado de São Paulo - Jordão, Alessandro Augusto (Universidade Federal de São Carlos, 2014)
The intensification of relations between universities and industry is revealed as a strategy for the strengthening innovation systems. For this reason, there has been a significant increase in the country of discussions in the universities and in the context of public policies on the most appropriate institutional mechanisms to encourage interaction between universities and industries. However, the creation of institutional mechanisms imposes a co-evolution to universities and industry which must be managed carefully so that the interaction can ensure technological results in the near term without compromising the developmental trajectories of knowledge in the long term. Supported by evolutionary and neo-Schumpeterian approach, and a historical approach to the technical and institutional co-evolution of the innovation system of the Brazilian oil industry, this research aimed explore the relationship between the Petrobras and the institutions of science and technology of the State of Sao Paulo through its Thematic Research Networks. Through an exploratory, descriptive and analytical study, this research revealed that, in linking actors with different (and complementary) innovative capabilities, through the Thematic Research Networks, the Petrobras has strengthened its technological acquis and at the same time afforded to science and technology institutions of the State of São Paulo knowledge production in scientific frontier areas. In addition, the Petrobras to promote, through its Thematic Research Networks, the creation of permanent and specific infrastructure research, improve infrastructure research existing and improve human resources specialized, the Petrobras has increased the capability research, development and innovation (RD&I) of different research groups of the science and technology institutions of the State of Sao Paul, qualifying research groups to attend regional technological demands.
The influence of academia-industry relations in technological development: a study of the relationship between Petrobras and the institutions of science and technology of the State of Sao Paulo.
Keywords: relação universidade-empresa; Petrobras; rede de pesquisa; inovação; parceria de pesquisa e desenvolvimento; inovações tecnológicas; university-industry relationship; Petrobras; network for innovation; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA::ECONOMIA DE TECNOLOGIA